Analisis Kandungan Faty Acid Metil Ester (Fame) Pada Biosolar B30 Dengan Metode Fourier Transform Infrared (Ftir) Studi Kasus Laboratorium PT. X. - Eka Megawati; Apriliya Prastika Anggraini; Resmihadi; Debora Ariyani (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2024)
The continuous and increasing use of fuel, causing depleting and non-renewable petroleum reserves, has the potential to cause an economic crisis in the future. With the current depletion of petroleum reserves, it can encourage efforts to find alternative fuels. Biodiesel is a type of alternative fuel that is environmentally friendly and can be renewed because it is made from vegetable oil (biodiesel) mixed with diesel oil. This research was conducted to determine the specifications for the content of Fatty Acid Methyl Ester (FAME) in biodiesel B30 using the Fourier Transform Infrared (FTIR) method produced at the Laboratory of PT. X. The results of the analysis of the Fatty Acid Methyl Ester (FAME) content of BioSolar B30 products at PT. X on March 25, 2021, the fame earned 30%, on April 7, 2021 the FAME content obtained 29% met the specifications (On Specifications) stipulated by the Decree of the Director General of Oil and Gas SK No. 146.K/10/DJM/2020. Keywords: B30, FAME, Fourier Transform Infrared (FTIR)